Travail, immigration et relations sociales à travers les parcours d’individus et familles d’une ville de l’Ancien Régime (Turin, xviiie siècle) - Beatrice Zucca Micheletto (L'Atelier du CRH)
This paper aims to use trial and justice archives, not to return to a social history of crime, but to question the system of norms and values at the core of professional paths (specifically crafts) of individuals and families that lived or stayed temporarily in Turin in xviiith century.Scholars who studied “work” traditionally focused on guilds archives and underlined stability and continuity of work in the artisan ateliers. Yet, this historiography let in the shadow some interesting social phenomenon, moreover the nature of relation between professional and personal paths of artisans in the city, time and way of exercising crafts, the role played by individual and family life-cycle. Finally, in this paper I suggest that through the study of two justice and trial archives (criminal and civil ones), where people are concerned in demonstrating their insertion and stability in the city compared with high mobility rates of the population, we can get a new image of the nature of work and relationship between the former and individuals in Ancien Régime urban environments.